2015
DOI: 10.1055/s-0035-1547771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between high normal TSH levels and metabolic syndrome components in type 2 diabetic subjects with euthyroidism

Abstract: a b s t r a c tObjective: Thyroid hormones as modulators of adaptive thermogenesis can potentially contribute to development of obesity. The purpose of our study is to observe a relationship between TSH and BMI, blood lipids, BP and HbA1c in type 2 diabetic subjects with euthyroidism. Methods: A total of 120 subjects with type 2 diabetes were recruited for this study from November 2012 to June 2014. Subjects were included in the study with TSH values between 0.4 and 4.5 mU/l, who did not take any thyroid medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As demonstrated in Table 2, glycemia or glycosylated hemoglobin might be positively 37,46,62,75,93,94,100,153 or negatively 33,66,76 associated with serum TSH levels. A positive association between TSH levels (or reduced thyroid function) and abnormal glucose metabolism may be related to the importance of the action of TH in different pathways related to glucose transport, especially those related to the expression of GLUT 4, as previously described.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 98%
See 2 more Smart Citations
“…As demonstrated in Table 2, glycemia or glycosylated hemoglobin might be positively 37,46,62,75,93,94,100,153 or negatively 33,66,76 associated with serum TSH levels. A positive association between TSH levels (or reduced thyroid function) and abnormal glucose metabolism may be related to the importance of the action of TH in different pathways related to glucose transport, especially those related to the expression of GLUT 4, as previously described.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 98%
“…However, the NCEPT/ATPIII was the most commonly applied criteria for diagnosis. 14,16,19,25,26,38,48,54,68,69,73,77,92,94,97,98,102 Other authors used the IDF criteria, 42,47,55,56,75,81,93 the World Health Organization or American Heart Association criteria, 45,62,79 or even local/regional or pre-established criteria defined by a joint interim statement. 29,45,52,76,96 Finally, some studies defined MetS by the presence of IR according to an abnormal Homeostatic Model Assessment of Insulin Resistance index (HOMA-IR) or euglycemic clamp result.…”
Section: Studies Evaluating the Association Between Metabolic Syndrommentioning
confidence: 99%
See 1 more Smart Citation
“…it's been found in T2DM female patients with normal thyroid function, TSH is positively correlated with TC and LDL-C, but it has no significant correlation with TG and HDL-C, but in male patients, TSH and TC, TG, LDL-C and HDL-C have no obvious correlation (24). Besides, it has found that in T2DM patients with normal thyroid function, TSH was positively correlated with TG and HbAlc (25), and it has no significant correlation with FBG, LDL-C and HDL-C, while FT3 and FT4 had no significant relations to glucose and lipid metabolism (26). Previous studies (27)(28)(29) have indicated that in T2DM patients, thyroid hormone levels are closely related to glucose and lipid metabolism, but there are few studies on the relationship between thyroid hormone levels and glucose and lipid metabolism in T1DM patients, especially in TIDM children with normal thyroid function.…”
Section: Discussionmentioning
confidence: 97%